Dietary lipid utilisation under different thermal conditions in flathead grey mullet (Mugil cephalus) - Silvia Natale; Federico Moroni; Ricardo Domingo-Bretón; Jaume Pérez-Sánchez; Marco Berrettini; Maria Giulia Ferrari; Francesco Dondi; Danilo Concu; Dario Vallainc; Stefano Carboni; Tomaso Patarnello; Pier Paolo Gatta; et al. (Frontiers in Marine Science, 2026)
Water temperature and dietary lipid levels are key factors influencing fish growth and metabolic homeostasis in aquaculture. This study aimed to understand the interactive effects on growth performance, metabolic response, gut microbiota, and gut evacuation dynamics in flathead grey mullet ( Mugil cephalus ). A 100-day feeding trial was carried out to assess the effects of two dietary lipid levels (10%, L10; 15%, L15) at 22 °C (LT) and 28 °C (HT). Specific growth rate (% day -1 ) was higher ( p < 0.05) at HT (0.90 ± 0.01 for both diets) than at LT (0.70 and 0.62 for L10 and L15, respectively). Feed intake at L15 diet was lower at both temperatures ( p < 0.05) while FCR was reduced only by HT and not by lipid levels. Serum metabolic profiling indicated that higher temperatures accelerated energy turnover, as evidenced by elevated serum glucose and lactate at HT across both dietary groups ( p < 0.05). Accordingly, fish at HT in both dietary treatments exhibited lower total protein and cholesterol ( p < 0.05), suggesting a more efficient utilisation of protein reserves and lipid processing to meet increased metabolic demands. Gut evacuation dynamics were described here for the first time in this species by sampling multiple intestinal sections at different time points (1, 3, 5, 7, 9, and 12 hours post-prandial). The intestine was almost completely empty by approximately 8 h post-prandial, with the notable exception of fish fed the HL diet at LT, where a significant delay in evacuation (18 h) was observed. This delay may be attributed to the combined effects of higher dietary lipid levels and lower temperatures, which both prolong digestion and intestinal transit times. Gut microbiota composition was primarily shaped by temperature, with a shift toward a specialised profile dominated by Cetobacterium at HT in both dietary groups. Overall, the results highlight that the combination of a 15% lipid diet and 28 °C was associated with the most positive outcomes among the tested conditions, providing further insight into how dietary composition and temperature modulate digestive physiology in flathead grey mullet.

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Dietary Paecilomyces variotii single-cell protein supports growth and intestinal health in gilthead sea bream - Serena Busti; Trond M Kortner; Elin Christine Valen; Elisa Benini; Alessio Bonaldo; Charilaos Xiros; Fabio Brambilla; Daniel Scicchitano; Giorgia Palladino; Marco Candela; Marco Berrettini; Francesco Dondi; et al. (Aquaculture, 2026)

Applying a regional certification scheme for aquatic invasive species fishery: The case of blue crab (Callinectes sapidus) in the northern Adriatic Sea - Sara Bonanomi; Simone Libralato; Loretta Malvarosa; Karolina Maria Czechowska; Giulia Sandalli; Alessia Cariani; Alice Ferrari; Ernesto Azzurro; Giuseppe Scarcella (Marine Policy, 2025)

Effect of simulated prolonged heat wave on biometric performance and HSP70 synthesis in the striped venus clam Chamelea gallina - Antonina De Marco; Vito Antonio Baldassarro; Maura Cescatti; Marzia Moretti; Laura Calzà; Luciana Giardino; Francesco Dondi; Maria Giulia Ferrari; Pier Paolo Gatta; Luca Parma; Alessio Bonaldo (Aquaculture, 2025)

Environmental, climatic, socio-economic factors and non-pharmacological interventions: A comprehensive four-domain risk assessment of COVID-19 hospitalization and death in Northern Italy - Lucia Palandri; Cristiana Rizzi; Vittoria Vandelli; Tommaso Filippini; Alessandro Ghinoi; Giuliano Carrozzi; Gianfranco De Girolamo; Isabella Morlini; Paola Coratza; Enrico Giovannetti; Margherita Russo; Mauro Soldati; et al. (International Journal of Hygiene and Environmental Health, 2025)

CCL18, CHI3L1, ANG2, IL-6 systemic levels are associated with the extent of lung damage and radiomic features in SARS-CoV-2 infection - Ilaria Ferrigno; Laura Verzellesi; Marta Ottone; Martina Bonacini; Alessandro Rossi; Giulia Besutti; Efrem Bonelli; Rossana Colla; Nicola Facciolongo; Elisabetta Teopompi; Marco Massari; Pamela Mancuso; et al. (Inflammation Research, 2024)

Life cycle assessment of lattice structures: Balancing mass saving and productivity - Giulia Colombini; Roberto Rosa; Anna Maria Ferrari; Silvio Defanti; Elena Bassoli (Journal of Cleaner Production, 2024)

Life cycle assessment of chemical synthesis of genistein and its glucosyl derivatives to be employed in the modulation of angiogenesis of hepatocellular cancer - Chiara Ruini; Luca Rigamonti; Aldo Zanni; Giulia Bertani; Gianluca Carnevale; Erika Ferrari; Paolo Neri; Anna Maria Ferrari; Roberto Rosa (Sustainable Chemistry and Pharmacy, 2023)

A multidisciplinary approach to estimating wolf population size for long‐term conservation - Francesca Marucco; Maria V. Boiani; Pierre Dupont; Cyril Milleret; Elisa Avanzinelli; Kristine Pilgrim; Michael K. Schwartz; Achaz von Hardenberg; Domenica Serena Perrone; Olivier P. Friard; Arianna Menzano; Francesco Bisi; et al. (Conservation Biology, 2023)
The wolf ( Canis lupus ) is among the most controversial of wildlife species. Abundance estimates are required to inform public debate and policy decisions, but obtaining them at biologically relevant scales is challenging. We developed a system for comprehensive population estimation across the Italian alpine region (100,000 km 2 ), involving 1513 trained operators representing 160 institutions. This extensive network allowed for coordinated genetic sample collection and landscape‐level spatial capture–recapture analyses that transcended administrative boundaries to produce the first estimates of key parameters for wolf population status assessment. Wolf abundance was estimated at 952 individuals (95% credible interval 816–1120) and 135 reproductive units (i.e., packs) (95% credible interval 112–165). We also estimated that mature individuals accounted for 33–45% of the entire population. The monitoring effort was spatially estimated thereby overcoming an important limitation of citizen science data. This is an important approach for promoting wolf–human coexistence based on wolf abundance monitoring and an endorsement of large‐scale harmonized conservation practices.

The Frequency of Intermediate Alleles in Patients with Cerebellar Phenotypes - Elena Capacci; Silvia Bagnoli; Giulia Giacomucci; Costanza Maria Rapillo; Alessandra Govoni; Valentina Bessi; Cristina Polito; Irene Giotti; Alice Brogi; Elisabetta Pelo; Sandro Sorbi; Benedetta Nacmias; et al. (The Cerebellum, 2023)
Cerebellar syndromes are clinically and etiologically heterogeneous and can be classified as hereditary, neurodegenerative non-hereditary, or acquired. Few data are available on the frequency of each form in the clinical setting. Growing interest is emerging regarding the genetic forms caused by triplet repeat expansions. Alleles with repeat expansion lower than the pathological threshold, termed intermediate alleles (IAs), have been found to be associated with disease manifestation. In order to assess the relevance of IAs as a cause of cerebellar syndromes, we enrolled 66 unrelated Italian ataxic patients and described the distribution of the different etiology of their syndromes and the frequency of IAs. Each patient underwent complete clinical, hematological, and neurophysiological assessments, neuroimaging evaluations, and genetic tests for autosomal dominant cerebellar ataxia (SCA) and fragile X-associated tremor/ataxia syndrome (FXTAS). We identified the following diagnostic categories: 28% sporadic adult-onset ataxia, 18% cerebellar variant of multiple system atrophy, 9% acquired forms, 9% genetic forms with full-range expansion, and 12% cases with intermediate-range expansion. The IAs were six in the FMR1 gene, two in the gene responsible for SCA8, and one in the ATXN2 gene. The clinical phenotype of patients carrying the IAs resembles, in most of the cases, the one associated with full-range expansion. Our study provides an exhaustive description of the causes of cerebellar ataxia, estimating for the first time the frequency of IAs in SCAs- and FXTAS-associated genes. The high percentage of cases with IAs supports further screening among patients with cerebellar syndromes.

Associations between serum gamma-globulin concentration, enzyme activities, growth and survival in preweaning Alpine goat kids - Mariana Roccaro; Marilena Bolcato; Maria Giulia Ferrari; Francesco Dondi; Arcangelo Gentile; Angelo Peli (Small Ruminant Research, 2023)

The leaching behaviors of lead, zinc, and sulfate in pyrite ash contaminated soil: mineralogical assessments and environmental implications - Yikai Liu; Simone Molinari; Maria Chiara Dalconi; Luca Valentini; Giulia Ricci; Claudio Carrer; Giorgio Ferrari; Gilberto Artioli (Journal of Environmental Chemical Engineering, 2023)

Prolonged heat waves reduce the condition index and alter the molecular parameters in the pacific oyster Crassostrea gigas - Antonina De Marco; Vito Antonio Baldassarro; Laura Calzà; Luciana Giardino; Francesco Dondi; Maria Giulia Ferrari; Giorgia Bignami; Luca Parma; Alessio Bonaldo (Fish & Shellfish Immunology, 2023)